Upaya Meningkatkan Literasi Membaca Siswa Kelas II SDN 2 Winduraja Menggunakan Metode Scramble (Penelitian Tindakan Kelas Di Kelas II SDN 2 Winduraja Dusun Hayawang Desa Winduraja Kecamatan Kawali Kabupaten Ciamis) - Nadhifah, Puji Aulia Hulwun; Maftuh, Ade; Zulkarnaen, Rizki Hadiwijaya (Jurnal Pendidikan Rafflesia, 2024)
The problem in this study is that most of the grade II students of SDN 2 Winduraja have low reading literacy skills, to improve reading literacy comprehension apply the scramble method. The scramble method is one of the language games that can help students not to be bored and comfortable when the learning process takes place. This classroom action research consists of two cycles, where each cycle consists of the stages of planning, implementation, observation and reflection. The method in this study used descriptive method. Data collection techniques using observation. Data collection tools use lesson plan observation sheet instruments, teacher activity assessment sheet instruments, student activity observation sheet instruments and reading literacy comprehension test results. The results of this study were in cycle I by 34.61% with an average score of 69.15 and in cycle II an increase of 11.53%, namely with an average score of 86.61. From the results obtained, it can be concluded that the use of scramble method can improve students' reading literacy comprehension.